Hubungan Tingkat Stres dengan Perilaku Pencegahan Stroke Pada Klien Hipertensi - Gede Ngurah (Jurnal Gema Keperawatan, 2020)
This research aims to know the relation between stress level with the stroke prevention behaviour on hypertensive clients in East Denpasar I Primary Health Center, Denpasar City on 2018. The type of research used is non-experimental research with correlational type and cross-sectional approach by using non probability sampling with purposive sampling. The number of samples is 176 people. Data collection used DASS 42 questionnaires and the stroke prevention behaviour. The research result shows that the most stress level is normal (39,5%), the most stroke prevention behaviour is good (77,8%). Hypothesis test used spearman test with p value is equal to 0,000 (α is equal to 0,05) and r value is equal to -0,60. The conclusion: there is significant relation between stress level with stroke prevention behaviour on hypertension clients in East Denpasar I Primary Health Center.